Effect of Monetary Aspects on the Performance of Islamic Banks in Indonesia - Panorama, Maya (International Journal of Economics and Financial Issues, 2017)
Actually, issue about Bank Performance is not special anymore. However, this topic in a dual banking system still an interesting issue. As in Indonesia, which have Islamic bank in a conventional economic system this Islamic Bank Performance (IBP) influence direct by monetary aspect. Using a quarterly panel data set from period 2001 until 2015; this research used econometric tools. Result shows that all variables are significantly affected. We prefer to used random effect that show the positive sign for Money Supply (MS), Exchange Rate (EXC) and Interest Rate (INTR) and negative sign for CPI. Then the result on Long term used ARDL Approach found that for PMG variable MS and INT have positive significant while EXC and CPI variable are negative significant. In MG estimates (Long term), MS, EXC and INTR are found to be positive significant while CPI variable have negative impact on IBP. Further more, in short time, PMG estimates result that MS and EXC shows negative impact and variables than have positive impact are CPI and INTR. While result in short run for MG estimates shows that MS, CPI and INTR have positive impact. Then EXC have negative impact. We suggest the government must always keep the monetary condition in a balance and healthy environment that support the development and improvement of Islamic Banking. Especially manage the INTR which is always have positive impact in all condition model. Keywords: Islamic Bank performance, CPI, Interest Rate, Money Supply, Exchange Rate JEL Classifications: E52, G21